Biodisel dari Minyak Nyamplung (Callophyllum inophyllum) dan Spiritus dengan Katalisator Kapur Tohor - Marnoto, Tjukup; Sulistyawati, Endang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
Production of biodiesel has been done by many institutions; however the materials used are usually competedwith food such as palm oil, therefore it has lesser economical value. The use of Callophyllum inophyllum plant inIndonesia is very limited and the seeds are usually thrown away the contain high oil relatively. This plant is relativelyeasy to grow and has seasonal fruiting mostly planted as shading plant in rural area and also as land slide resistingplant. The plant is normally utilized for light construction and burning wood. The technology for producing biodieselis simple and can be easily introduced to the society. Biodiesel produced from easily obtained and low costmaterials will improve a society’s energy independency and well-being. This paper presents the process of producingbiodiesel from Callophyllum inophyllum oil and rubbing alcohol using superficial lime (CaO) as the solid catalystthat is cheap and easily obtained, therefore this technology can be easily transferred to the society and willimprove the economical value of the plant. Referring to the varieties used, relatively good condition was at 1:3 molratio of Callophyllum inophyllum oil to rubbing alcohol and the amount of catalyst used was 0.3-0.5% of the rubbingalcohol. Physical characteristics of the produced biodisel were such as specific gravity at 60/600F was 0.870, flashpoint P.M.cc was 1950C and pour point was 40C.